Magnesium and Its Role in Primary Open Angle Glaucoma; A Novel Therapeutic? - Elghobashy, Mirna; Lamont, Hannah C.; Morelli-Batters, Alexander; Masood, Imran; Hill, Lisa J. (Frontiers in Ophthalmology, 2022)
Glaucoma is the leading cause of irreversible blindness globally, with Primary open angle glaucoma (POAG) being the commonest subtype. POAG is characterized by an increase in intraocular pressure (IOP), leading to optic nerve damage and subsequent visual field defects. Despite the clinical burden this disease poses, current therapies aim to reduce IOP rather than targeting the underling pathogenesis. Although the pathogenesis of POAG is complex, the culprit for this increase in IOP resides in the aqueous humour (AH) outflow pathway; the trabecular meshwork (TM) and Schlemm’s canal. Dysfunction in these tissues is due to inherent mitochondrial dysfunction, calcium influx sensitivity, increase in reactive oxygen species (ROS) production, TGFβ-2 induction, leading to a sustained inflammatory response. Magnesium is the second most common intracellular cation, and is a major co-factor in over 300 reactions, being highly conserved within energy-dependent organelles such as the mitochondria. Magnesium deficiency has been observed in POAG and is linked to inflammatory and fibrotic responses, as well as increased oxidative stress (OS). Magnesium supplementation been shown to reduce cellular ROS, alleviate mitochondrial dysregulation and has further antifibrotic and anti-inflammatory properties within ocular tissues, and other soft tissues prone to fibrosis, suggest that magnesium can improve visual fields in patients with POAG. The link between magnesium deficiency and glaucoma pathogenesis as well as the potential role of magnesium supplementation in the management of patients with POAG will be explored within this review.